Analisis of Digital Literacy, Empowering Leadership, Proactive Personality on Work Creativity - Muhammad Nazri Raihan; Dicky Jhoansyah; Resa Nurmala (Dinasti International Journal of Education Management And Social Science, 2024)
In this era of disruption, the development of technology is accelerating, and people's habits in accessing information have changed. Initially, people accessed information through newspapers, magazines, television, radio, and so on. But over time, information can now be accessed through social media and online networks. So this is a big challenge for print media companies that are transforming to online media to survive and compete with other companies work creativity is an important thing to be applied by media companies, one of which is Radar Sukabumi. This study aims to determine the effect of digital literacy, empowering leadership, and proactive personality on work creativity in Radar Sukabumi employees. The sampling technique used is saturated sample technique where the entire population is sampled. Data analysis used multiple linear regression using SPSS Version 26. The results showed that digital literacy has a positive and significant effect on work creativity, then empowering leadership has a positive and significant effect on work creativity. In addition, proactive personality also has a positive and significant effect on work creativity. This shows that all independent variables have a positive and significant effect on the dependent variable.